(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2014)
Age in laymen’s view is the time passed after birth and ageing is a continuous process in human as well as in all other living beings. The problems of age estimation in living/dead person are mostly encountered by police and it is a subject matter of great medico-legal and academic interest. Some work for accurate estimation of age has been done in this country, which exhibit differences in different parts of this country. This study includes radiological examination of clavicle of 100 individuals for the study of fusion of ossification centre of medial end of clavicle in the age group of 18–23 years of both sexes in RNT Medical College, Udaipur, Rajasthan.